2000
DOI: 10.1097/00006534-200009020-00019
|View full text |Cite
|
Sign up to set email alerts
|

Crossover Replantation and Fillet Flap Coverage of the Stump after Ectopic Implantation: A Case of Bilateral Leg Amputation

Abstract: A successful case of crossover replantation of the left foot to the stump of the right leg and temporary ectopic implantation of the right amputated foot on the forearm is described. The ectopically implanted right foot was used as a free fillet flap for the late reconstruction of the left leg stump. At the latest follow-up examination, 18 months after the accident, the patient was able to walk independently with a prosthesis on the stump of the left leg. Both the cross-replanted foot and the free filleted foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The contralateral forearm has been used as a temporary recipient for digital replantation, 5,6 penile replantation, 4 and complex foot cross-over replantation. 7 The contralateral posterior tibial vessels were used recently by Wang et al 8 for foot replantation. The femoral vessels have been reported only once as temporary recipients by Sheridan and Wood 9 in a transhumeral amputation.…”
Section: Discussionmentioning
confidence: 99%
“…The contralateral forearm has been used as a temporary recipient for digital replantation, 5,6 penile replantation, 4 and complex foot cross-over replantation. 7 The contralateral posterior tibial vessels were used recently by Wang et al 8 for foot replantation. The femoral vessels have been reported only once as temporary recipients by Sheridan and Wood 9 in a transhumeral amputation.…”
Section: Discussionmentioning
confidence: 99%
“…He presented with an incomplete degloving of the soft tissue envelope of the volar and dorsal hand from the junction of the middle and distal third of the forearm to the palm (Figs. 4,5). He had multiple fractures through the MCP joints of digits 2 through 5 with loss of perfusion to these digits.…”
Section: Casementioning
confidence: 99%
“…One group reported on use of a branch of the ulnar artery as a recipient vessel 11 ; others suggested use of the radial artery, often in end-to-end fashion. 5,6,8,9,13,15 Some of these authors cited the use of the radial artery for additional arterial conduit length upon transfer of the part back to its orthotopic position. The contralateral upper extremity has often been selected to keep the part distant from the site of reconstruction and away from mobile joints.…”
Section: Ideal Location Of Ectopic Bankingmentioning
confidence: 99%
“…Kayikcioglu et al 7 reported a successful case of salvage of a lower extremity that was injured by a train accident. The left foot was crossover-replanted to the stump of the right leg, and the right amputated foot was temporarily implanted ectopically onto the forearm, which was used as a tissue bank for later soft-tissue reconstruction.…”
Section: à6mentioning
confidence: 99%
“…Graf et al 5 and Kayikcioglu et al 7 thought that an implantation in the groin or axilla may have the disadvantage of a short vascular pedicle. Mobility of the hip may cause problems in the postoperative period.…”
Section: à6mentioning
confidence: 99%